2019
DOI: 10.12968/hmed.2019.80.6.325
|View full text |Cite
|
Sign up to set email alerts
|

Total hip arthroplasty in obesity: separating ‘fat’ from fiction

Abstract: Obesity is a modern-day epidemic with increasing prevalence that is directly impacting the global burden of primary total hip arthroplasty. The risk of requiring total hip arthroplasty for osteoarthritis increases incrementally with increasing obesity class. Surgical intervention in obese patients presents a set of unique challenges that should be recognized by the treating medical team. Although predominantly satisfactory outcomes have been reported, perioperative anaesthetic and surgical concerns require tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…THA is considered the gold standard in the treatment of end-stage hip OA. Compared to non-obese patients, overweight and obese individuals undergoing THA are usually younger and present a higher risk of perioperative complications [ 53 ]. Indeed, obesity is a multisystemic disease often accompanied by several comorbidities that may increase the likelihood of intra- or post-procedural adverse events [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…THA is considered the gold standard in the treatment of end-stage hip OA. Compared to non-obese patients, overweight and obese individuals undergoing THA are usually younger and present a higher risk of perioperative complications [ 53 ]. Indeed, obesity is a multisystemic disease often accompanied by several comorbidities that may increase the likelihood of intra- or post-procedural adverse events [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, while being convenient to the surgeon to reduce bleeding, intraoperative hypotension should be avoided in patients with a previous ischemic stroke due to the higher risk of cerebral hypoperfusion and recurrent ischemic events [ 60 ]. In addition, intraprocedural issues concerning airway management and alterations of vital signs in this subset of patients may occasionally require the surgeon to stop operating until the situation is under control [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been controversy over whether obesity has impact on THA. We reviewed many works of literature on the effects of obesity on THA, the conclusions of which are not uniform or even contradictory, holding opposite views [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is undoubtedly a lifestyle disease; yet, there is ample evidence that social determinants of health are key risk factors that may inhibit patients from losing weight before surgery. For instance, people without college educations are twice as likely to be obese than their college educated counterparts [7]. Additionally, lower socioeconomic status is associated with higher rates of obesity.…”
mentioning
confidence: 99%
“…Additionally, lower socioeconomic status is associated with higher rates of obesity. Interestingly, one study found that simply moving out of a highly impoverished neighborhood significantly reduced the odds of developing this disease [7]. Finally, ethnicity is associated with obesity, as African American and Hispanic communities face disproportionately higher rates of obesity than non-Hispanic Caucasians [8,9].…”
mentioning
confidence: 99%